MEMBENTUK KEMATANGAN EMOSI REMAJA MELALUI PENDIDIKAN JASMANI DAN OLAHRAGA DI SEKOLAH - Jaka Sunardi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
Teenagers are part of the society who have duties and responsibilities of their life, such as, follow the lesson in the school that called learning activities or school in common term. A failure occurs caused by unmaturity of the teenagers emotion. Unstable emotion caused by the difficulties to concentrate and affect to the learning achievement, meanwhile, the learning process is needed to absorb the materials learned for be raised again some times. Physical education, sport and health given because it have comprehensive goals include physical aspect, cognitive, affective, emotional, social and moral. Physical education is a process of interaction between students and the environment which managed through the systematic physical activity to perform whole human being, developing physical aspect, psychomotor, cognitive and affective. The maturity of emotion include: being realistic, accept ourselves and other what it is, well adjustment,be able to resolve an issues in objective ways, not depend on the others, concern with ethical values and morals, having empathy, sense of humor, have creativities and like a challanges. All aspects of emotional maturity can be formed through physical education, sport and health. Keywords : Emotional maturity, Adolescents, Physical education, sport and health